Optimalisasi Geometri Wedge pada Pesawat Teleterapi 60Co - Putri, Ajeng Sarinda Yunia; Suharyana, Suharyana; Riyatun, Riyatun; Muhtarom, Muhtarom (Universitas Sebelas Maret, 2017)
Abstract: In RSUD Dr. Moewardi available wedge angle of 15°, 30°, 45°, and 60°. This research simulates with Monte Carlo N-Particle eXtended Version (MCNPX) computer software to determine the geometry of the wedge that produces the isodose angle of 20°, which is hoped to be applied to therapy of organ tilt of 20 ° in some cases of cervical cancer. In simulation obtained the value of the wedge factor of isodose angle of 20° and distribution of dose rate. The simulated material of wedge is Lead-Antimony Alloy. Verification of the simulation result was done by measuring the wedge factor of angle of 30° and 60°, the simulation result was validated with result of measurement experiment on 60Co teletherapy in RSUD Dr. Moewardi Surakarta. The relative error between simulation and measurement experiment of wedge angle of 30° is 8.84% and angle of 60° is 4.35%. The relative error is small to convince the researcher to develop a simulation at an isodose angle of about 20°. From the simulation results obtained isodose angle 20.3° of Lead-Antimony Alloy material with geometry is length 16 cm, width 14.9 cm, thick 0.83 cm, the value of the angle α of 3.2°. Wedge factor of isodose angle of 20.3 ° is (0.68 ± 0.01). Wedge isodose angle of 20.3° if used in therapy in an organ tilt about 20 ° gives dose rate enough uniform. Abstrak :. Di RSUD Dr. Moewardi tersedia wedge untuk sudut 15°, 30°, 45°, dan 60°. Penelitian ini mensimulasikan dengan software computer Monte Carlo N-Particle eXtended Version (MCNPX) untuk menentukan geometri wedge yang menghasilkan sudut isodosis 20°, dimana diharapkan dapat diaplikasikan pada terapi organ dengan kemiringan 20° di beberapa kasus kanker serviks. Besaran yang diperoleh dari simulasi adalah nilai faktor transmisi wedge sudut isodosis 20° dan distribusi laju dosis serap penggunaan wedge tersebut. Bahan wedge yang disimulasikan adalah Lead-Antimony Alloy. Verifikasi hasil simulasi dilakukan dengan pengukuran faktor wedge pada sudut isodosis 30° dan 60°, hasil simulasi divalidasi dengan hasil pengukuran langsung pada pesawat teleterapi 60Co di RSUD Dr. Moewardi Surakarta. Kesalahan antara simulasi dan pengukuran langsung pada isodosis sudut 30° adalah 8,84 % dan pada sudut 60° adalah 4,35 %. Kesalahan relatif tersebut cukup kecil sehingga meyakinkan peneliti untuk menyusun simulasi pada sudut sekitar 20°. Dari hasil simulasi diperoleh isodosis sudut 20,3° dari bahan Lead-Antimony Alloy dengan geometri yaitu panjangnya 16 cm, lebarnya 14,9 cm, tebalnya 0,83 cm, nilai sudut α sebesar 3,2°. Faktor wedge sudut 20,3° sebesar (0,68 ± 0,01). Wedge sudut isodosis 20,3° bila digunakan dalam terapi pada organ dengan kemiringan 20° memberikan laju dosis yang cukup seragam.